Rat tissue responses to dacarbazine-containing implants made of cross-linked polyurethane of different densities - N. A. Galatenko; R. A. Rozhnova; D. V. Kuliesh; V. D. Denisenko; A. P. Maletskyy; N. M. Bigun (Ukrainian Society of Ophthalmologists, 2022)
Background: Restorative orbital and periorbital surgeries require implantable materials containing antimicrobial and anticancer medications. Purpose: To assess rat tissue responses to dacarbazine-containing implants made of cross-linked polyurethane of different densities. Material and Methods: Dacarbazine (DC)-containing polyurethane-urea foam (PUUF) implants were a subject of research. We studied the dynamics of DC release from these implant samples. Soft tissue cellular responses to the developed composites were assessed through the implantation of the latter in Wistar rats. Results: We found that the number of open pores impacts implant survival. There was no substantial difference in DC release between the PUUF samples with a DC weight percent of 1% and those with a DC weight percent of 0.5% at incubation days 1 to 3. At days 5, 7 and 14, an increase in DC release was higher in the former samples than in the latter samples (64% versus 55%). In animals with a subcutaneously implanted PUUF sample, there was histological evidence of (a) formation of a capsule and tight network of blood vessels surrounding an implanted sample at day 3, and (b) separation of the implanted material from the surrounding tissues by a wide cuff of lymphocytes and a thick connective tissue capsule (CTC) at day 7. Conclusion: The number of open pores impacts DC release and the speed of connective tissue ingrowth into the porous matrix. It was found that a CTC formed around all implants at early time points and at day 30, which in combination with the presence of DC in composite materials resulted in long-term cellular inflammation at the implant placement site.